NEW FOSSIL EPHEMEROPTERA AND COLEOPTERA FROM THE LADINIAN(MIDDLE TRIASSIC) OF CANTON TICINO (SWITZERLAND) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2001)
Two insects are described from the sediments of the uppermost Ladinian (Middle Triassic) of Meride (Canton Ticino, Switzerland). Tintorina triassica gen. n. sp. n., a representative of a new family, Tintoriniidae, of the Ephemeroptera, is described on the basis of two specimens, one being almost complete; a single elytron is ascribed to Notocupes sp. ind. (Cupedidae, Coleoptera). The ephemeroptera specimens possibly belong to a previously unrecognized Triassic suborder/order within the infraorder Ephemeroidea. Apart from the taxonomic interest of this find, it is pointed out that these are the first fossil insects found in the classic deposits of Monte San Giorgio-Besano, famous mostly for its vertebrates. The presence of Ephemeroptera confirms the existence of land with adjacent fresh-water basins where the preservation of many organisms in fine-grained matrix was possible.